Sistem Waralaba Dalam Kaidah Maslahah Mursalah - Joko Hadi Purnomo (JES (Jurnal Ekonomi Syariah), 2017)
Franchising is a business of cooperation among the parties. One party is called a franchisor and another party is called the franchisee to increase market penetration, growing new businesses and open working opportunity. Maslahah mursalah is used to address and answer new issues and developments that arise due to the progress of science and modern technology, both in setting the law against new problems, no provision of law and a new law to replace the old laws that do not conform any more with the circumstances, situations, conditions and welfare of the people of today. Maslahah mursalah is one method of laws istinbath that is made hujjah. For examples of problems set by maslahah mursalah ruling, it is shown that laws enacted by the method is more nurturing and more able to realize the sharia objectives, and it is the effectiveness of maslahah mursalah in setting the Islamic rules. Franchise system has a lot of benefit. Although not perfect, but overall it gives any favor by minimizing business risks, taking maslahah and keep madharat. The franchise system, of course, has been in accordance with the rules of maslahah mursalah. Keywords: Franchising, Business, Maslahah Mursalah